DETERMINATION OF RESISTANCE FORCES FROM MANDIBULAR MOVEMENTS THROUGH DYNAMIC SIMULATION USING KINEMATIC ANALYSIS AND FINITE ELEMENTS METHOD - Mihaela Vătu; Monica Mihaela Crăițoiu; Daniela Vintilă; Veronica Mercuț; Sanda Mihaela Popescu; Monica Scrieciu; Dragoș Laurențiu Popa (Romanian Society of Oral Rehabilitation, 2018)
Aim of the study This study aimed to evaluate the resistance forces that develop in the dental structures of the two left upper premolars during mandibular movements, through dynamic simulation using the kinematic analysis and the finite elements method. Material and methods For this, using several softwares, we obtained a virtual model of the jaw that was attached to a virtual skull. For all the components of the skull and of the dento-maxilar apparatus mechanical properties were given. The movements as mandibule lifting, propulsion, retropulsion and laterality were simulated. Results The study highlighted the presence of resistance forces in the dental structures with values ​​between 31.781 N in the retropulsion movement and 174.104 N in the lateral movement. Conclusions These values ​​are close to the occlusive forces values in the conditions of a balanced occlusion.